2023
DOI: 10.3390/cryst13040674
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Multiband Metamaterial Microstrip-Based Radiating Structure Design Showing High Gain Performance for Wireless Communication Devices

Abstract: High-speed wireless communication devices need antennas to operate at multiple frequencies with high gain. The need for such antennas is increasing day by day. The proposed metamaterial superstrate antenna gives a high gain and multiband performance, which is required in high-speed wireless communication devices. The designed antenna is also applicable for C- and X-band communication devices. The structure consists of a simple patch and multiple split-ring resonator metamaterials on the superstrate region. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Ensuring the orthogonality of antenna channels and averting signal degradation requires effective management and mitigation of crosspolar interference. Engineers can design systems that optimize spatial diversity, reduce interference, and improve overall communication reliability and capacity by comprehending and adjusting both the crosspolar and copolar characteristics of MIMO antennas [54].…”
Section: Resultsmentioning
confidence: 99%
“…Ensuring the orthogonality of antenna channels and averting signal degradation requires effective management and mitigation of crosspolar interference. Engineers can design systems that optimize spatial diversity, reduce interference, and improve overall communication reliability and capacity by comprehending and adjusting both the crosspolar and copolar characteristics of MIMO antennas [54].…”
Section: Resultsmentioning
confidence: 99%
“…In Sub-6 GHz infrastructure, the network quality and channel capacity can be improved with the multiple input multiple output (MIMO) systems with a wider bandwidth and therefore this technology has become a research hotspot of the decade [1]. Recently, an ample amount of MIMO antenna research has been reported in the literature covering the Sub-6 GHz 5G band [2][3][4][5][6][7][8][9][10][11][12][13]. Most of the literature exhibits a trade-off between less bandwidth, gain or higher mutual coupling that hinders its application in realtime MIMO applications.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature exhibits a trade-off between less bandwidth, gain or higher mutual coupling that hinders its application in realtime MIMO applications. Increasing the thickness of the substrate results in increasing the bandwidth, since the fringing fields alters the distance between the radiating edges and consequently lower the Q-factor and improves the bandwidth [8,9]. However, increasing the substrate thickness decreases the comfort of users and hinders its suitability in wearable applications.…”
Section: Introductionmentioning
confidence: 99%